The Effect of Financial Inclusion on Inequality Income in East Java - Vita Venia; Shochrul Rohmatul Ajija (Kantor Perwakilan Bank Indonesia Provinsi Jawa Timur, 2024)
This study analyzes the impact of financial inclusion on the level of income inequality 38 districts/cities in East Java from 2015 to 2021. Using the Generalized Method of Moment (GMM) analysis, its is known that financial inclusion has a negative influence on the level of income inequality in East Java. That is, the more financially inclusive in East Java, the lower the income inequality that occurs. Based on these results, the efforts that have been taken so far by the East Java government to increase financial inclusion must continue to be increased so as to reduce the level of income inequality between districts/cities in the province.